The process of physiotherapy in patients treated for colorectal cancer - Agnieszka Filarecka; Maciej Biernacki; Michał Jęchorek; Łukasz Leksowski; Michał Małek; Robert Tysowski; Karolina Molek; Magdalena Tysowska; Karolina Szymura (Journal of Education, Health and Sport, 2021)
Breast cancer is a global problem, causes many deaths worldwide, and the emergence of disability resulting from treatment.